1970
DOI: 10.1038/bjc.1970.15
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetic of Cellular Proliferation in Human Tissues. Determination of Duration of DNA Synthesis Using Double Labeling Autoradiography

Abstract: SUMMARY.-The duration of the DNA synthesis period in normal and malignant human tissues from the larynx, trachea bronchus and esophagus of 13 patients has been estimated by a tritiated thymidine, carbon-14 thymidine double-labeling method in vitro. The DNA synthesis times range from approximately 10 to 25 hours, are shortest in normal tissues, and are longer in malignant tumor cells than in benign tumor cells. The double-labeling method, the analysis of thymidine labeling index data for the measurement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1971
1971
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Because the nasal vestibular region is the first site ofinteraction of toxic and infectious agents with the respiratory system, the epithehum lining this area may often be subjected to injurious challenges, thus requiring more active regenerative processes. It is also noteworthy that, like the lower gastrointestinal tract, the nasal mucosa is normally colonized by a microbial flora and may be subject to a similarly rapid epithelial cell turnover (12,13) in contrast to the relatively slower turnover occurring in the normally sterile lower respiratory tract (14). Furthermore, parallel observations of human and experimental animal tracheal epithelium revealed that PNP arrays do occur in normal airway epithelium lining the lower respiratory tract, however, they are generally less abundant than in nasal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Because the nasal vestibular region is the first site ofinteraction of toxic and infectious agents with the respiratory system, the epithehum lining this area may often be subjected to injurious challenges, thus requiring more active regenerative processes. It is also noteworthy that, like the lower gastrointestinal tract, the nasal mucosa is normally colonized by a microbial flora and may be subject to a similarly rapid epithelial cell turnover (12,13) in contrast to the relatively slower turnover occurring in the normally sterile lower respiratory tract (14). Furthermore, parallel observations of human and experimental animal tracheal epithelium revealed that PNP arrays do occur in normal airway epithelium lining the lower respiratory tract, however, they are generally less abundant than in nasal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…These observations also support the experimental design of the present study inasmuch as they suggest that this experimental protocol provides a transient, stable, rapidly incorporated, and detectable pool of available isotope. In another study (Fabrikant, 1970), the period of DNA synthesis in human airway epithelium was determined to be on the order of 10-25 hr. This finding also may provide some insight into the extended period required for ciliated cells to appear with label.…”
Section: Discussionmentioning
confidence: 99%